2018
DOI: 10.1073/pnas.1803530115
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for MTR4–ZCCHC8 interactions that stimulate the MTR4 helicase in the nuclear exosome-targeting complex

Abstract: SignificanceAberrant or unwanted transcripts can be degraded by the RNA exosome with the help of the nuclear exosome-targeting (NEXT) complex. NEXT, composed of RNA-binding protein RBM7, scaffold ZCCHC8, and helicase MTR4, is implicated in stress response, neurodegeneration, and viral ribogenesis. Here, we characterize the activities of NEXT that support its role in exosome-mediated decay. NEXT catalyzes 3′→5′ helicase activity and disrupts RNA:RNA and DNA:RNA duplexes more efficiently than MTR4. Optimal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 53 publications
6
66
0
Order By: Relevance
“…A recent study reported that both NRDE2 and MTR4 negatively affects DNA damage responses in mammalian cells (Richard et al 2018), indicating that NRDE2 could cooperate with MTR4 in some other biological processes that are independent of CBC/ZFC3H1 and the exosome. In line with this, similar to previous finding with ZCCHC8 (Puno and Lima 2018) and Trf4/Air2 (Jia et al 2012), NRDE2 binding enhances in vitro RNA-binding properties and helicase activity of MTR4. How these proteins, including NRDE2, enhance MTR4 helicase activity remains unknown.…”
Section: Nrde2 Ensures Efficient Nuclear Mrna Exportsupporting
confidence: 92%
See 2 more Smart Citations
“…A recent study reported that both NRDE2 and MTR4 negatively affects DNA damage responses in mammalian cells (Richard et al 2018), indicating that NRDE2 could cooperate with MTR4 in some other biological processes that are independent of CBC/ZFC3H1 and the exosome. In line with this, similar to previous finding with ZCCHC8 (Puno and Lima 2018) and Trf4/Air2 (Jia et al 2012), NRDE2 binding enhances in vitro RNA-binding properties and helicase activity of MTR4. How these proteins, including NRDE2, enhance MTR4 helicase activity remains unknown.…”
Section: Nrde2 Ensures Efficient Nuclear Mrna Exportsupporting
confidence: 92%
“…Based on the data that NRDE2 enhances RNA binding affinity and helicase activity of MTR4 by similar fold, we speculate that this might be due to enhanced RNA binding ability. Together with studies reported by Puno and Lima (2018) and Jia et al (2012), we speculate that MTR4 alone exhibiting limited RNA binding ability might be due to the hindrance of the flexible Arch domain. When in complex with ZCCHC8, Trf4/ Air2 or NRDE2, the Arch domain is positioned at more favorable orientations for RNA binding.…”
Section: Nrde2 Ensures Efficient Nuclear Mrna Exportsupporting
confidence: 81%
See 1 more Smart Citation
“…This gene has already been shown to be differentially expressed between depressed women and controls [38] (see S4B Fig). Furthermore, SKIV2L2 has been implicated in the stress response and neurodegeneration through the nuclear exosome-targeting (NEXT) complex [39].…”
Section: Qtl Network Analysesmentioning
confidence: 99%
“…This gene has already been shown to be differentially expressed between depressed women and controls 51 (see Supplementary Figure 6). Furthermore, SKIV2L2 has been implicated in the stress response and neurodegeneration through the nuclear exosome-targeting (NEXT) complex 52 .…”
Section: Qtl Network Analysesmentioning
confidence: 99%